Pengembangan Sistem Mata Kuliah Manajemen Proyek Teknologi Informasi dengan Metode Agile - Astuti, Nur Rochmah Dyah Puji; Anwar, Nuril; Sakirno, Muhammad Bayu Aji (Building of Informatics, Technology and Science (BITS), 2021)
The work course at Ahmad Dahlan University's Informatics Engineering is a course that aims for students to go directly or get projects related to technology development. One of the creative courses that students must take in semester 6 is Information Technology Project Management (MPTI), where the course is conducted in groups. Processing of final grades from MPTI courses from 3 components, namely supervisors, examiners and industry supervisors (partners). Because the value components are from various sources, a system is needed to process all processes from registration to processing the final value. The agile development method is a development method that prioritizes input from partners as users, besides that the agile method has advantages including fast, adaptive, iterative. The model used in system development in agile is the Dynamic Systems Development Method. Data collection was done by literature study, observation, and interviews. The system development stage using an iterative model includes the needs analysis stage, the design stage, the implementation stage, the testing stage, and the evaluation stage. Implementation using the PHP programming language and the Laravel framework. Testing is done black box test. The results of the research produced an information system and tested. Tests carried out using a black box test which resulted in 82,76%